LEGAL PROTECTION FOR BANKS AGAINST NON-CERTIFIED LAND COLLATERAL - Dina Mardiana; Yenny Eta Widyanti; Reka Dewantara (CV. RADJA PUBLIKA, 2025)
This study examines legal protection for banks in facing bad loans with non-certificate land as collateral, particularly in the context of distributing Working Capital Credit (KMK) to MSMEs. In banking practice, non-certificate land such as girik, petok D, or segel is still widely used as collateral even though it does not meet the formal requirements as an object of Mortgage Rights as regulated in Law Number 4 of 1996. This condition creates vulnerability for banks as creditors, because non-certificate land documents only function as proof of control, not proof of rights, so they do not have executorial power. This study uses a normative juridical method with a statutory and conceptual approach to examine the gap between positive law and banking practice. The results show that preventive legal protection for banks is reflected in the provisions on collateral assessment, the bank's obligation to apply the principle of prudence, and the bank's internal regulations regarding credit risk mitigation. Repressive legal protection is realized through legal remedies that can be taken if the debtor defaults, including through simple lawsuits, risk transfer through debt acknowledgment agreements, and civil execution based on debt-receivable relationships. This study also formulates a conceptualization of dispute resolution that includes mediation, credit restructuring, and litigation as a last resort. The results of this study confirm that the use of non-certificate collateral requires strengthened regulations and harmonization between agrarian and banking law to ensure legal certainty and protection for creditors.